Elevated CO2 ameliorate the negative effects of high temperature on groundnut (Arachis hypogaea)- Studies under free-air temperature elevation - M. Vanaja; P. Sathish; N. Jyothi Lakshmi; G. Vijay Kumar; P. Vagheera; Ch. Mohan; S.K. Yadav; B. Sarkar; M. Maheswari; K. SAMMI REDDY (Journal of Agrometeorology, 2019)
Four groundnut (Arachis hypogaea L.) genotypes- Narayani, Dharani, K-6 and K-9 were assessed for growth and yield responses at elevated temperature of 3.0 ± 0.5°C above ambient canopy temperature (eT) and its interaction with elevated CO of 550 ± 50ppm (eT+eCO ) under Free Air 2 2 Temperature Elevation (FATE) facility. The study revealed that eT significantly decreased photosynthetic rate (A ) of all groundnut genotypes whereas eT+eCO condition ameliorated the ill effects of eT. The net 2 impact of eT on A was higher than transpiration rate (Tr) and this reflected in decreased WUE with all net genotypes. WUE improved significantly at eT+eCO with increased A and decreased Tr. Increase in 2 net canopy temperature (eT) resulted decreased relative water content (RWC), cell membrane stability and increased osmotic potential, Malondialdehyde (MDA) content and accumulation of proline. Elevated CO 2 along with eT (eT+eCO ) facilitated these parameters to recover to that of ambient controls, revealing the 2 ameliorative effect of eCO . Similar responses were recorded for biomass and yield parameters. Among 2 the selected groundnut genotypes, superior performance for seed yield at high temperature of >40°C by K-9 was due to ability to maintain better reproductive capacity and Dharani was responsive to elevated CO even at high temperature, indicating the genotypic variability.